How we continue bonds with deceased persons: The proximity-seeking behavior scale. Issue 2 (7th February 2023) - Eisma, Maarten C.; Nguyen, Linh T. H.
Abstract: Continuing bonds is a multifaceted process, encompassing perceptions, beliefs, illusions and hallucinations, and overt behaviors. We developed the Proximity-Seeking Behavior Scale (PSBS) to assess overt behavior to continue bonds with the deceased person. We had 694 bereaved adults complete an online survey. Exploratory and confirmatory factor analyses yielded a one-factor model for PSBS items. PSBS reliability was good. PSBS scores correlated positively with rumination and yearning, feeling connected to the deceased person, and prolonged grief and depression symptoms. The PSBS appears a reliable and valid instrument to assess proximity-seeking behaviors.